Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Keterampilan Berpikir Kreatif Peserta Didik Fase E SMAN 2 Bayang pada Materi Bioteknologi - Bunda, Indah Permata; Anggriyani, Ria; Selaras, Ganda Hijrah; Rahmatika, Helsa (TSAQOFAH, 2025)
Creative thinking skills are essential competencies that students must possess to meet the challenges of the 21st century; however, students in Phase E at SMAN 2 Bayang still demonstrate low proficiency in this area. This deficiency is attributed to suboptimal student-centered learning and limited variation in instructional models. This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ creative thinking skills in the biotechnology topic. The research employed a Randomized Control Group Posttest Only Design experimental method, with the population consisting of all Phase E students and purposive sampling applied to select Phase E.9 as the experimental class and Phase E.5 as the control class. The research instrument was a set of nine essay questions with a validity score of 91.1, and data were analyzed using the Mann-Whitney U test. The results showed that the average creative thinking score of students in the experimental class (6.75) was significantly higher than that of the control class (4.73), with a significance value of 0.000 < 0.05. These findings indicate that the PBL model has a significant effect on improving students’ creative thinking skills. The practical implication of this result is that the PBL model can be adopted as an effective instructional strategy to develop higher-order thinking skills, particularly in biotechnology learning at the senior high school level.